Force Field Analysis: Sebuah Rencana Strategis Pengembangan Badan Usaha Milik Desa - Soejono, Djoko; Zahrosa, Dimas Bastara; Maharani, Ariq Dewi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Force Field Analysis (FFA) has been widely used by organization development practitioners to plan and implement organizational changes. The research was conducted with the aim of formulating a development strategy for Village-Owned Enterprises (BUM Desa). The research location was determined purposively, namely in BUM Desa Pasirian Raharjo according to the recommendation of the Lumajang Regency Government. BUM Desa Pasirian Raharjo is located in Pasirian Village, Pasirian District, Lumajang Regency, East Java Province. Business units managed by BUM Desa Pasirian Raharjo are waste processing, savings and loan units, MSMEs, and the tourism sector. Data were analyzed using the FFA approach by considering the driving factors for the development of BUM Desa and the factors inhibiting the development of BUM Desa. The results showed that the key driving factor was that BUM Desa had formal legality (Village Regulations and AD/ART), while the key inhibiting factor was weak support from the RT and RW levels. The research conclusion is in the form of recommendations for the development strategy of BUM Desa by strengthening synergy with community organizations at both the RT and RW levels, so that the problem of waste management does not only have an impact on social aspects.